INFLUENCE OF FOOD INTAKE ON THE EVENT DIABETES MELLITUS IN THE WORK AREA OF HEALTH CENTER WOTU DISTRICT WOTU IN 2021 - Muhammad Risal (Homes Journal = Hospital Management Studies Journal, 2021)
Background:Diabetes mellitus is a metabolic disorder characterized by abnormal blood sugar levels in a person, this disease can attack several organs of the body causing various kinds of complaints. Food intake is food and drink that is consumed at a certain time when someone needs it. Objective:This study aims to determine the relationship or influence of food intake on the incidence of Diabetes Mellitus in the work area of the Wotu Health Center, Wotu District.Method: The research design used was cross-sectional. The population in this study amounted to 68 respondents who suffered from Diabetes Mellitus at the Wotu Public Health Center, Wotu District in 2021. The sampling technique used was consecutive sampling and obtained a sample of 40 respondents. The data collected in this study were data on food intake, blood sugar levels, age, gender, and occupation. Pearson correlation test was used when analyzing data. Result:The results of the study of the most prevalence of normal blood sugar levels in respondents were 42.5%, where respondents with good food intake were 40%, the results of the analysis using the Pearson Correlation test showed that the p-value was 0.000 smaller than the alpha value (0.05) so that it could be stated that Ho was rejected, which means that there is an effect of food intake on the incidence of diabetes mellitus in the working area of the Wotu Public Health Center, Wotu District.  Conclusion:This study is that there is an effect of food intake on the incidence of diabetes mellitus in the work area of the Wotu Public Health Center, Wotu District